How Do Diabetes Models Measure Up? A Review of Diabetes Economic Models and ADA Guidelines - Lindsay Govan; Olivia Wu; Robert Lindsay; Andrew Briggs (Journal of Health Economics and Outcomes Research)
**Introduction:** Economic models and computer simulation models have been used for assessing short-term cost-effectiveness of interventions and modelling long-term outcomes and costs. Several guidelines and checklists have been published to improve the methods and reporting. This article presents an overview of published diabetes models with a focus on how well the models are described in relation to the considerations described by the American Diabetes Association (ADA) guidelines.